An anatomical study of the nerves targeted for sensory blocks of the head and neck in neonates and infants - Van Schoor, Albert-Neels (University of Pretoria, 2018)
The father of modern regional anaesthesia, Gaston Labat, made this very important statement: “Anatomy is the foundation upon which the entire concept of regional anaesthesia is built. Anyone who wishes to be an expert in the art of regional anaesthesia must be thoroughly grounded in anatomy.” This statement is as true today, as in 1922 when it was first made. Adult anatomy applicable to regional anaesthesia has been extensively investigated, resulting in the improvement of techniques and a decrease in complications. However, in the paediatric population, in most cases, the anatomy of adults are used and disproportionately modified in order to perform paediatric regional anaesthetic techniques. This is not considered favourable, and can lead to failed blocks or complications. Therefore, knowledge of the anatomy of paediatric patients is not only required, but considered vital for the successful performance of regional nerve blocks in paediatric patients. The overall aim of this research study was, therefore, to effectively describe the paediatric anatomy of five head and neck nerve blocks commonly performed, based on dissections and measurements of paediatric formalin-fixed cadavers, as well as osteological samples. Based on easily identifiable bony~ and soft tissue landmarks, easily performed techniques are proposed in order to safely and successfully perform these regional nerve blocks in paediatric patients. This will not only minimise possible opioid-related complications, but will ensure optimal management of postoperative pain. In conclusion, the importance of anatomical knowledge applicable to the paediatric population is beyond discussion, and techniques based on the applicable neonatal and infant anatomy will not only educate and facilitate doctors during the performance of these regional nerve blocks, but will also greatly benefit the paediatric patients undergoing these procedures.